Corrosion Crack Nucleation Mechanism in the Welded Structures of X65 Steel in Natural Seawater - Linyue Bai; Lei Gao; Kebin Jiang (Advances in Materials Science and Engineering)
The nucleation mechanism of corrosion cracks in welded structures in natural seawater has been revealed through investigation on the corrosion behavior of X65-welded structures in natural seawater. The evolution laws of surface corrosion morphology, residual stress, and areas of welded structures with the most serious corrosion damage were analyzed by microstructure observation, corrosion morphology observation, residual stress detection, and magnetic field detection. The results show that the main factors of determining surface corrosion morphology evolution law of welded structures are microstructures of the weld joint, heat-affected zone (HAZ), and the fusion line. Due to the difference of corrosion rates between the weld joint, HAZ, and the coarse Widmänstatten structure in fusion line, the fusion line of welded structures receives the most serious damage while being corroded. Meanwhile, mutual reinforcement of residual stress and corrosion damage on the surface of welded structures further accelerate the nucleation of corrosion cracks. Under the influences of microstructure, residual stress, and corrosion, corrosion cracks that are parallel to weld joints generate first in the fusion line of welded structures. Therefore, it makes welded structures the source of marine steel structures’ corrosion failure.